Mandelic acid derived ionic liquids: synthesis, toxicity and biodegradability. Issue 4 (12th January 2017) - Prydderch, Hannah; Haiβ, Annette; Spulak, Marcel; Quilty, Brid; Kümmerer, Klaus; Heise, Andreas; Gathergood, Nicholas
Abstract : Novel ionic liquids have been synthesised directly from the renewable resource mandelic acid and evaluated for their antimicrobial activity and biodegradability. Abstract : A series of ten ionic liquids (ILs) was synthesised from the renewable resource mandelic acid. The ILs showed low antimicrobial activity towards the thirteen bacterial and twelve fungal strains they were screened against. A general trend of increasing bacterial toxicity in the order methyl ester < ethyl ester < n -butyl ester/amide was observed. IL biodegradability was evaluated using the Closed Bottle test (OECD 301D). Biodegradation increased in the order of increasing alkyl chain length for the ester ILs (methyl < ethyl < n -butyl). Despite none of the ILs presenting as readily biodegradable (>60% in 28 days), a series of biodegradation transformation products has been proposed based on the degradation of the ester/amide alkyl chain. This data has allowed for an assessment of the effect of IL structural features on toxicity and biodegradation, particularly allowing for a comparison to earlier work where additional oxygen atoms were present to facilitate biodegradation and attenuate toxicity. The mandelic acid derived ILs did not pass the Closed Bottle test (OECD 301D) and can be included in the rules of thumb for the design of biodegradable ILs.